1989
DOI: 10.1115/1.3168382
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Comparative Study of St. Jude Medical and Edwards-Duromedics Bileaflet Valves Using Laser Anemometry

Abstract: An in vitro comparative study of St. Jude (SJ) and Edwards-Duromedics (DM) Bileaflet valves was performed under steady and physiological pulsatile flow conditions in an axisymmetric chamber using Laser Doppler Anemometry (LDA). LDA measurements were conducted in two different orientations; in the first orientation, the LDA traverse was perpendicular and, in the second orientation, parallel to the tilt axis of the leaflets. The axial velocities were measured in both orientations at two different locations dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Therefore, it may be considered favorable to the VAD design. Although there is still a conflict between researchers regarding the advantage of any of the MHV type implanted in the natural heart, 10,14,33 in the configuration of VAD both our results and the experiments by Yin et al found the monoleaflet valve (placed in an S-shape conduit) to be beneficial over the bileaflet valve.…”
Section: Discussioncontrasting
confidence: 58%
“…Therefore, it may be considered favorable to the VAD design. Although there is still a conflict between researchers regarding the advantage of any of the MHV type implanted in the natural heart, 10,14,33 in the configuration of VAD both our results and the experiments by Yin et al found the monoleaflet valve (placed in an S-shape conduit) to be beneficial over the bileaflet valve.…”
Section: Discussioncontrasting
confidence: 58%
“…So far many studies for the improvement of the design of the mechanical heart valve prosthesis have been reported. Some of them are on the blood flow passing through the leaflet for a single cycle with inelastic artery wall [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this clinically accepted axiom has not been proved analytically as yet. Only one reference [3] showed that the curved leaflet geometry used in the Edwards Duromedics MHV prosthesis does not provide any fluid dynamic advantage. Hence, the purpose of this paper is to analytically prove and/or justify that the bileaflet MHV with flat leaflet geometry is structurally stronger than the bileaflet MHV prosthesis with curved leaflet geometry by using the numerical analysis method (i.e., FEM).…”
Section: Introductionmentioning
confidence: 98%